O transtorno do espectro autista (TEA): impactos da legislação para uma prática pedagógica inclusiva - Melo, Pedro Henrique Silva de Souza (Brasil, 2025)
The article’s main objective was to investigate the legislation of Inclusive Education pertinent to Autism Spectrum Disorder (ASD) and its implications for a democratic pedagogical practice. Acting as school support for children with autism, in the municipal network of Manaus, and with the deepening of the Brazilian legislation of Inclusive Education, it has been observed that children with Autism Spectrum Disorder have faced many challenges in regular public schools with regard to the form of specialize pedagogical and technical care, despite the numerous laws that ensure their citizenship rights. In the vast majority of times they are isolated in the classrooms, without individualized care by the teacher, or relying only on school support to accompany them in some basic needs. This is a bibliographic study with a qualitative approach. It brings in its structure an initial approach to literacy and literacy from the perspective of cognitive and linguistic work with a focus on Autism Spectrum Disorder, permeating the concepts and conceptions about ASD, the legislation of Special and Inclusive Education related to ASD. A consistent analysis is also made of which didactic - pedagogical resources are guided by the manuals of the education secretariats for the care of children with ASD. As a result, the study showed in the dialogue with the authors in the area of Inclusive Education, such as Mantoan (2003) and Liberalesso (2020), the clear relationship between the early stimulation of the child with ASD and the development of reading and writing skills. Through the analysis of some didactic-pedagogical materials, researchers such as Gomes (2015) and pedagogical collections of Semed de São Paulo/SP (2021), a range of possibilities for pedagogical practice in different teaching and learning situations was found.